New cause of penicillin treatment failure. Issue 6067 (16th April 1977) - Barnes, P; Waterworth, P M
Abstract : A large empyema infected with a penicillin-sensitive haemolytic group B streptococcus failed to respond to high doses of penicillin. After two weeks' treatment the pus aspirated was found not only to contain no penicillin, but also to inactivate penicillin added to it. We believe that the inactivating agent is an enzyme that may destroy various penicillins and cephalosporins but has no effect on other common antibiotics. When treatment was changed to doxycycline the patient made a rapid recovery.